Mechanical properties and marginal fit of prefabricated versus customized dental implant abutments: A comparative study. (31st August 2022) - Ma, Mingchen; Li, Xuejing; Zou, Liyan; He, Jing; Zhao, Baohong
Abstract: Introduction: Dental implant abutments play an important role in the health and aesthetics of soft and hard tissues around implants. Purpose: To compare mechanical properties and marginal fit of prefabricated and customized dental implant abutments and provide references to evaluate the relationship between abutment choice and clinical indications. Methods: Titanium abutments were randomly divided into prefabricated and customized abutments. Static and dynamic loads were applied according to ISO14801:2016. Mechanical properties, including fracture strength, fatigue strength, rotational torque value, and torque loss rate, were measured. The biological properties of the implant abutments were assessed using an internal marginal fit. The samples were sliced, and the internal marginal fit was examined using a scanning electron microscope before and after cyclic loading. The length of the tight contact was calculated at the level of the conical connection, lower internal connection, and screw threads. Microleakage was evaluated by immersing the samples in 1% methylene blue and measuring the absorbance. Results: The fracture strengths of the prefabricated abutments were greater than those of the customized abutments before and after cyclic loading. The average fatigue strengths of the prefabricated and customized abutments were 350 and 300 N, respectively. The removal torque loss of the customized abutments was significantly greater than that of the prefabricated abutments. Significant differences were found in conical connection before loading, while the screw threads showed substantial differences between the two groups after loading. Microleakage in the customized abutments was significantly higher than that in the prefabricated abutments before and after loading. Conclusions: Prefabricated abutments showed superior mechanical and biological properties compared with customized abutments in vitro, suggesting a greater risk of mechanical and biological complications occurring with the use of customized abutments. This study provides a reference for the clinical selection of implant abutments.